Kafaah dalam Pernikahan Endogami Pada Komunitas Arab di Kraksaan Probolinggo - Ahmad Muzakki (Program Pascasarjana Universitas Ibrahimy, 2017)
In Tradition of Habaib obligation similarity nasab in forbidden marriage between syarifah women and non Sayyid men because there is not kufu` between they and not continue of nasab by Rasulullah.The purpose of this study was to determine the views tradition of marriage Syarifah in Arabic village Kraksaan Probolinggo and to determine factor of forbidden marriage between syarifah women and non Sayyid men perspective Islamic law. Based on the results of research the traditional views of marriage Syarifah in Arabic village Kraksaan Probolinggo same of tradition other habaib that is forbidden marriage between syarifah women and non Sayyid men because there is not kufu` between they. And other factor cause obligation similarity nasab in marriage Syarifah in Arabic village Kraksaan Probolinggo is factor of ancestry, social and religion followed. In this problem there is difference between ulama of four madzhab about similarity nasab in marriage Syarifah. According to Malikiyah kafaah just in religion, while three madzhab kafaah nasab is important component in marriage, then Syafi`iyyah and Hanabilah obligation of marriage between Syarifah women and non Sayyid men for keep noble and continue of nasab.